Topographical regulation of stem cell differentiation by plant-derived micro/nanostructures. Issue 35 (1st September 2020) - Zhang, Ruitong; Han, Shuwei; Ren, Na; Liang, Linlin; Liang, Na; Liu, Fan; Chen, Yuke; Li, Dong; Liu, Wenxia; Liu, Hong; Sun, Chunhui
Abstract : A novel plant-derived material as scaffolds that can promote the osteogenic differentiation of human adipose-derived stem cells is reported. Abstract : This study examines the osteogenic differentiation promotion effect of micro/nanostructures of raffia on human adipose-derived stem cells to confirm the potential application of plant-derived micro/nanotopographies in tissue regeneration. The results confirm that the nanorod array on the front surface and the honeycomb-like microstructure on the back surface of raffia can not only regulate the adhesion, spreading, and migration of stem cells but also promote the osteogenic differentiation of the stem cells at a subsequent stage of cell culture. The osteocalcin expressions by the 21-day cultured cells on the front and back surfaces of raffia were 55-fold and 36-fold higher compared to the expression on a tissue culture plate. This indicates that plant-derived micro/nanotopographies can significantly promote stem cell differentiation. Furthermore, a general strategy for the application of plant-derived materials to stem-cell differentiation and bone-tissue engineering is suggested.